Acoso escolar en Cuba. ¿Qué dicen las investigaciones? / School bullying in Cuba. What does the research say? - Yoanka Rodney Rodríguez; Mirta Veneranda García Leyva (Novedades en Población, 2020)
In recent years there has been a growing interest in investigating the behaviour of the different manifestations of violence in Cuban educational institutions. Although in most cases their causes are described and explored, and the role of teaching staff is also recognized, the prevention of this problem is insufficiently studied even today. Approaching some of the investigations that directly had school violence as their object of study in Cuba from the nineties of the 20th century to the present day, and identifying those that address bulling, will allow us to have a certain vision of the complexity of the phenomenon. Systematizing the research carried out could give a vision of what aspects of the phenomenon of school bullying have been studied and in which others it would be necessary to deepen. That is why we will reflect on some of the investigations that have addressed the subject in Cuba. Resumen En los últimos años se ha hecho manifiesto un mayor interés por investigar el comportamiento de las diferentes manifestaciones de violencia en las instituciones educacionales cubanas, y aunque en la mayoría de los casos se describen y exploran sus causas, también se reconoce el papel del profesorado en la prevención de dicha problemática, insuficientemente estudiada aún en la actualidad. Acercarse a algunas de las investigaciones que directamente tuvieron a la violencia escolar como su objeto de estudio en Cuba desde finales de los 90 del siglo XX hasta la actualidad e identificar aquellas que abordan el acoso escolar, permitirá tener una cierta visión de la complejidad del fenómeno. Sistematizar las investigaciones realizadas podría dar una visión de qué aspectos del fenómeno del acoso escolar han sido estudiados y en qué otros sería necesario profundizar, en aras de la prevención de este flagelo social, es por ello que reflexionaremos sobre qué plantean algunas de las investigaciones que han abordado la temática en Cuba.